Association of Genetic Polymorphisms in Base excision Repair Pathways and Cervical Cancer Risk Factors in a Tertiary Care Centre - Charles, Mark Rector; Raza, Syed Tasleem; Pratap, Pushpendra; Eba, Ale (Asian Pacific Journal of Cancer Biology, 2024)
Background and Objective: Cervical cancer is one of the most frequent neoplastic disorders affecting women, with about half a million new cases diagnosed globally each year. Reduced DNA repair capacity (DRC) is linked to an increased risk of cancer, particularly cervical cancer. DNA repair gene polymorphisms may play a role in genomic instability and carcinogenesis. Cervical cancer is linked to a number of risk factors that have been verified. The goal of this study was to compare genotypes of DNA repair genes XRCC1-194, XRCC1-280, XRCC1-399, and XRCC3-241 with distinct histological subtypes in patients and controls. Material and Methods: To test this theory, 168 cervical cancer patients with histological confirmed cases and 184 healthy control women were inducted in the study. For genotyping we used CTPP method (Arg194Trp, Arg280His, and Arg399Gln & XRCC3-T241M). Results: A positive association was observed between the polymorphisms of XRCC1 genes, that is, in codons 194 [P=0.03, odds ratio (OR) =2.39, 95% confidence interval (CI)=5.2–1.1], 280 (P=0.01, OR=4.1, 95% CI=11.5–1.3), and 399 (P=0.01, OR=3.4, 95% CI=8.6–1.3) in cervical cancer As well as risk factor like early age of pregnancy, high number of parity are also likely to be contributing in disease development. Conclusion: Our results suggested that, XRCC1399 gene is an important candidate gene for susceptibility to cervical cancer. Although the sample size was small, the present study indicate a statistical association between cervical cancer and XRCC1 SNPs. Future studies are needed that may provide a better understanding of the association between gene polymorphism and cervical carcinoma risk factors are assessed.